Effects of Pleuran (β-glucan from Pleurotus ostreatus) Supplementation on Incidence and Duration of Bronchiectasis Exacerbations - Minov, Jordan; Stoleski, Sasho; Karadzinska-bislimovska, Jovanka; Petrova, Tatjana; Vasilevska, Kristin; Mijakoski, Dragan; Jesenak, Milos (Scientific Foundation SPIROSKI, Skopje, Republic of Macedonia, 2020)
BACKGROUND: Patients with non-cystic fibrosis bronchiectasis (BE) have frequent exacerbations that are causes of significant morbidity and sometimes mortality, and which it is desirable to prevent. AIM: We aimed to assess the effects of pleuran on the incidence and duration of exacerbations in patients with BE. METHODS: A prospective, observational, open-label, and active-controlled study was realized as a comparison of the frequency and duration of exacerbations between a group of patients with BE (30 patients, 14 males and 16 females, aged 44–72 years) who received a combination supplement containing pleuran 100 mg, Vitamin C 60 mg and zinc 5 mg over a 3-month period and a group of patients with BE (31 patients, 15 males and 16 females, aged 45–74 years) treated over a 3-month period with a combination supplement containing Vitamin C 60 mg and zinc 5 mg. RESULTS: Over the study period, altogether 46 exacerbations were documented (19 in the patients receiving pleuran and 27 in the patients who did not receive pleuran), nine of which required hospital treatment (four in the patients receiving pleuran [21.5%] and five in the patients who did not receive pleuran [18.6%]). The mean number of exacerbations over the study period was significantly lower in the patients receiving pleuran (0.6 ± 0.4) as compared to the mean number in the patients who did not receive pleuran (0.8 ± 0.3) (p = 0.0297). The mean duration of exacerbations, expressed in days, needed for cure or clinical improvement in the patients receiving pleuran (11.2 ± 1.7 days) was significantly shorter than that of exacerbations in the patients who did not receive pleuran (12.4 ± 1.3 days) (p = 0.0029). We found significantly lower incidence and significantly shorter duration of exacerbations in the patients with BE who received pleuran as compared to their incidence and duration in the patients with BE who did not receive pleuran. CONCLUSION: Our findings indicated a need for further investigations in this domain to define the possible role of pleuran in the prevention of BE exacerbations.
Keywords: Bronchiectasis; Duration; Exacerbation; Incidence; Pleuran